We Get by With a Little Help From Our PEERS: The Practice Enhancement, Engagement, Resilience, and Support Program for Building Community and Well-Being in Medical Education. (15th March 2022) - Feingold, Jordyn H.; Kaplan, Carly A.; Hart, Anne; Waldman, Rachel; Kronman, Hope; Brody, Jason; Hargrove, Jacqueline; Hurtado, Alicia; Simon, Asher B.
Abstract : Problem: Physician distress is a growing national problem that begins in medical school. Solutions that teach well-being concepts and coping skills during medical school and throughout medical training are needed. Approach: The Practice Enhancement, Engagement, Resilience, and Support (PEERS) program was designed at the Icahn School of Medicine at Mount Sinai (ISMMS) in 2017 as a longitudinal program for medical students to process challenges and learn evidence-based coping strategies in a supportive group setting. The curriculum comprises 10 small-group sessions incorporating principles of mindfulness, positive psychology, cognitive behavioral therapy, and dialectical behavioral therapy. Students remain with the same group of approximately 8 students throughout the PEERS program, which spans all 4 years of medical school. As an established part of the core medical school curriculum, PEERS centers physician well-being as an essential clinical skill for providing sustainable, high-quality patient care. Outcomes: Now in its fourth year, PEERS is recognized as an effective, sustainable intervention to support trainee well-being. Cross-sectional survey data collected in 2020 reveal that PEERS has effectively established a space for emotional support and community building among peers and mentors. The program has successfully garnered institutional and administrative support, including protected curricular time and dedicated faculty leadership. Next Steps: PEERS continues to evolve, incorporating feedback in real time to reflect the changing landscape of medical education, particularly in the era of remote learning. Given the demand for well-being initiatives throughout the Mount Sinai Health System, PEERS programming is being adapted and implemented across various residency, fellowship, and graduate school programs at ISMMS with the support of Mount Sinai's Office of Well-Being and Resilience and the Office of Graduate Medical Education. The PEERS program offers an evidence-based, trainee-led model that can be flexibly implemented at medical training programs across the country to support trainee well-being.